B Cells and Autoantibodies in Multiple Sclerosis - Anne-Katrin Pröbstel (International Journal of Molecular Sciences, 2015)
While over the past decades T cells have been considered key players in the pathogenesis of multiple sclerosis (MS), it has only recently become evident that B cells have a major contributing role. Our understanding of the role of B cells has evolved substantially following the clinical success of B cell-targeting therapies and increasing experimental evidence for significant B cell involvement. Rather than mere antibody-producing cells, it is becoming clear that they are team players with the capacity to prime and regulate T cells, and function both as pro- and anti-inflammatory mediators. However, despite tremendous efforts, the target antigen(s) of B cells in MS have yet to be identified. The first part of this review summarizes the clinical evidence and results from animal studies pointing to the relevance of B cells in the pathogenesis of MS. The second part gives an overview of the currently known potential autoantigen targets. The third part recapitulates and critically appraises the currently available B cell-directed therapies.